POPULASI BAKTERI PADA RUMPUT LAUT (Eucheuma Cottonii) YANG TERSERANG PENYAKIT ICE-ICE - S Supatno; Wahyu Andy Nugraha; I Insafitri (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2010)
The period of sea-weed growing under low condition is a problem that is generally faced by the farmers. The spreading of ice ice disease is affected by the environment changes that suppress the sea-weed growing and become the cause of organic substances releasing, MUCUS on thallus and also stimulate the presence of bacteria around the plantation area. The aim of this research is to know the population of bacteria on E. cottonii infected by ice-ice disease at different location. The method used in the measurement of the population bacteria is total ﬁat analysis (TFA). Data collection was done three times weekly on three different places Lobuk village, Bluto sub district, Sumenep. The result of observation shows that the average of bacteria population on those three different locations and also different time-observing are signiﬁcantly different. The total average of bacteria populations ranges from 7278 to 18060 coloni/gr. The high value of this population is assumed as a part of the environment parameter that supports the growing of E. cottonii such as temperature and velocity.Keywords : Bacteria population, Ice-ice, E. cottonli